Analysis of Legal and Social Implications Related to the Visa Free Policy for Visiting Foreign Citizens: A Meta-Analysis in Bali, Indonesia - Sahril Muhamad Maulani; Nur Rizki, Radha Evi (HM Publisher, 2024)
The free visit visa (BVK) policy for foreign nationals (WNA) in Bali, Indonesia, has become an important instrument in encouraging tourism. However, this policy also gives rise to complex dynamics of social norms. This research aims to analyze existing studies regarding social norms related to BVK in Bali through a meta-analysis approach. This research uses a meta-analysis method by collecting data from various relevant empirical studies, both qualitative and quantitative, published between 2018-2024. Keywords used in the search included